Penerapan Qur’an, Fun, and Quality dalam Pembentukan Karakter Islami pada Anak Usia Dini di Kelompok Bermain dan Taman kanak-kanak AnakQu - Wulandari, Retno (ACIECE, 2019)
This study is entitled Application of the Qur'an, Fun, and Quality in the formation of Islamiccharacter in early childhood in the PlayQu and Kindergarten Group. It aims to find out how toapply the Qur'an, Fun, And Quality in Playgroup and Kindergarten Children. This research uses descriptive qualitative method. Data collection techniques are by interviewing, documenting and observing and analyzing data with data reduction flow, data display, and verification / conclusion. The AnakQu Play Group / Kindergarten conducts fun and Quranic early childhood education, which aims to balance aspects of children's general knowledge and character. So that children have Islamic skills and character in accordance with the Qur'an. The results showed that the application of the Qur'an, Fun, And Quality in every learning process in early childhood in the Playgroup and Kindergarten Children could form Islamic characters